ANALISA PENGARUH TUNDA JUAL GABAH KERING PANEN TERHADAP PENDAPATAN PETANI PADI DI DESA KARANG BINANGUN BELITANG MADANG RAYA OKU TIMUR - Munsirum (Jurnal Bakti Agribisnis, 2018)
The purpose of this study is to determine the amount of income obtained by farmers who sell grain directly after harvest and farmers who delay selling grain and to find out the difference in income of farmers who sell unhulled grain directly after harvest with farmers who delay selling grain. This research was conducted using a survey method. Sampling of farmers who postpone selling grain and storing them waiting until the price of grain is high was carried out by using the census method for all populations totaling 17. Meanwhile, sampling of farmers who directly sell grain to 17 farmers from 374 populations was carried out using purposive sampling method with criteria respondents are farmers who have their own land with a land area of> 0.5 Ha. The results showed that the average production cost for the farmers to postpone selling GKP was IDR 12,911,329 / Ha / MT, the income was IDR 23,215,058 / Ha / MT, so that the income was IDR 10.303,729 / Ha / MT The production costs for direct selling GKP farmers are IDR 12,107,847 / Ha / MT, revenue is IDR 21,527,265 / Ha / MT, so you get an income of IDR 9,419,417 / Ha / MT. The average income of the respondent's delay in selling GKP was higher than that of the respondent who was selling GKP directly with the average difference in income of IDR 884,312 / Ha / MT. The R-C value of the delay in selling GKP is 1.80, while the direct selling value is 1.78. Statistically, there is a significant (significant) difference between the income of the respondent with the delay in selling GKP and the respondent from selling GKP directly. This can be seen from the t value of 3.42 and the t value of 2.036.